Cuprous sulfide and nickel disulfide positive electrode material based on two-dimensional nanosheet wrapped three-dimensional cube, preparation method of cuprous sulfide and nickel disulfide positive electrode material and lithium-magnesium dual-ion battery

By using two-dimensional nanosheets to wrap three-dimensional cubes of cuprous sulfide @ nickel disulfide cathode material and 0.4M APC-0.4M LiCl electrolyte, the problem of poor cycle stability of lithium-magnesium dual-ion batteries is solved, and the effects of high specific capacity, excellent cycle life and good rate performance are achieved.

CN119695102AActive Publication Date: 2025-03-25ANHUI NORMAL UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411838985.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-25
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

The circulation stability of lithium-magnesium dual-ion batteries is poor, and the prior art is difficult to effectively solve this problem.

Method used

Cu2S@NiS2 composite was prepared by solvothermal method to form a unique structure of nanosheet-encapsulated cubes.

Benefits of technology

It significantly improves the cycle stability of lithium-magnesium dual-ion batteries, increases the specific capacity, optimizes the rate performance, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119695102A_ABST
    Figure CN119695102A_ABST
Patent Text Reader

Abstract

The invention provides a cuprous sulfide and nickel disulfide positive electrode material based on a two-dimensional nanosheet coated three-dimensional cube, a preparation method of the cuprous sulfide and nickel disulfide positive electrode material and a lithium-magnesium dual-ion battery, and the preparation method comprises the following steps: firstly, directionally forming a Cu2O cube by using a copper salt, an alkaline solution and D (+)-glucose under a water bath condition of 70 DEG C; then, Cu2O, a nickel source, a sulfur source and a surfactant are subjected to solvothermal synthesis, and a two-dimensional and three-dimensional combined structure of a Cu2S cube wrapped by NiS2 nanosheets is formed. The two-dimensional and three-dimensional combined structure can shorten the particle transmission path, achieves the effect of rapid charging and discharging, provides more active sites, increases the specific surface area, makes full contact with electrolyte, and improves the cycle stability of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of positive electrode materials for lithium-magnesium dual-ion batteries, and specifically relates to a cuprous sulfide@nickel disulfide (Cu2S@NiS2) positive electrode material based on two-dimensional nanosheets wrapping three-dimensional cubes, a preparation method thereof, and a lithium-magnesium dual-ion battery, wherein the electrolyte used is a 0.4M APC-0.4M LiCl electrolyte. Background Art

[0002] With the continuous development of the new energy industry, the demand for the development of energy storage materials is increasing. Among them, lithium-ion batteries (LIB) are widely used in many fields due to their high capacity, high potential and long life, especially in new energy vehicles, electronic equipment, military industry and other fields. However, due to the shortage of lithium resources, high cost, safety anxiety and other issues, scientists continue to explore alternatives to lithium-ion batteries.

[0003] In recent years, magnesium ion batteries (MIBs) have attracted great attention due to their low price, safety, no dendrite generation during charge and discharge, and high volumetric capacity (3832 mAh cm -1 ) and other advantages have attracted widespread attention. However, Mg 2+ The strong polarization effect inhibits the diffusion of ions in solid materials. In order to take into account the advantages of LIB and MIB, more and more research is being done on constructing Mg / Li mixed ion batteries (MLHBs). This battery system combines the fast kinetics of Li + Combined with a dendrite-free Mg anode.

[0004] So far, cathode materials for MLHBs have been widely studied. Among them, transition metal sulfides (TMCs) are considered to be a promising electrode material with high theoretical capacity, low cost and phase transition mechanism. Therefore, it is necessary to provide a high-performance cathode material for MLHBs. Summary of the invention

[0005] The purpose of the present invention is to provide a cuprous sulfide@nickel disulfide positive electrode material based on two-dimensional nanosheets wrapping three-dimensional cubes and a preparation method thereof, wherein Cu2O cubes are prepared using low-cost raw materials, and a Cu2S@NiS2 complex of three-dimensional cubes wrapped by two-dimensional nanosheets is obtained by a one-step solvothermal method, and the preparation method is simple; the product has a novel structure, high yield and low cost.

[0006] Another object of the present invention is to provide a lithium-magnesium dual-ion battery, which uses the prepared cuprous sulfide@nickel disulfide positive electrode material based on two-dimensional nanosheets wrapping three-dimensional cubes as the electrode material and 0.4MAPC-0.4M LiCl as the electrolyte to improve the poor cycle stability of the lithium-magnesium dual-ion battery.

[0007] The specific technical solutions of the present invention are as follows:

[0008] A method for preparing a cuprous sulfide@nickel disulfide positive electrode material based on two-dimensional nanosheets encapsulating three-dimensional cubes comprises the following steps:

[0009] 1) Preparation of Cu2O cubes;

[0010] 2) Cu2O cubes, nickel source, sulfur source and surfactant are mixed in an organic solvent and subjected to solvothermal treatment to obtain Cu2S@NiS2.

[0011] In step 1), the method for preparing Cu2O cubes is: disperse the copper source in water, add alkaline solution dropwise thereto, stir, add reducing agent, and heat to react to obtain the result.

[0012] In step 1), the molar ratio of the copper source, the alkali in the alkaline solution and the reducing agent is 1:5-7:0.2-0.4;

[0013] In step 1), the copper source is a soluble copper salt, preferably Cu(CH3COO)2·H2O;

[0014] In step 1), the alkaline solution is a NaOH solution with a concentration range of 4 to 8 M, preferably 6 M;

[0015] In step 1), the reducing agent is (D+)-glucose;

[0016] In step 1), the concentration of the copper source in water is 0.2-0.4 mol / L;

[0017] In step 1), the water is deionized water;

[0018] In step 1), the reducing agent is added after stirring, the stirring speed is 300-800 rpm, and the stirring time is 5 minutes;

[0019] In step 1), the heating reaction means: carrying out the reaction in a water bath at 70°C for 1 hour; the entire process in step 1) is carried out in a water bath at 70°C;

[0020] In step 2), the mass ratio of the Cu2O cube to the nickel source is in the range of 2:1 to 1:2, preferably 1:2;

[0021] In step 2), the mass ratio of the nickel source, the sulfur source and the surfactant is 4:3-5:60-80;

[0022] In step 2), the nickel source is Ni(NO3)2·6H2O, the sulfur source is thioacetamide (TAA), and the surfactant is polyvinylpyrrolidone (PVP, average molecular weight 8000, K16-18);

[0023] In step 2), the concentration of the nickel source in the organic solvent is 0.01-0.02 mol / L;

[0024] In step 2), the organic solvent is ethylene glycol;

[0025] In step 2), the solvent thermal reaction is carried out at 160-200° C. for 18-24 h, preferably at 200° C. for 18 h.

[0026] The present invention provides a cuprous sulfide @ nickel disulfide positive electrode material based on a three-dimensional cube wrapped in a two-dimensional nanosheet, which is prepared by the above method. The cuprous sulfide @ nickel disulfide positive electrode material based on a three-dimensional cube wrapped in a two-dimensional nanosheet has a size of 4 to 6 μm, wherein Cu2S is the core and NiS2 is the shell; the outer NiS2 nanosheet has a thickness of 70±5 nm for each layer of the nanosheet.

[0027] The Cu2S@NiS2 material of a three-dimensional cube wrapped in a two-dimensional nanosheet prepared by the present invention is prepared by first using copper salt, alkaline solution and D(+)-glucose in a water bath at 70°C to orient the Cu2O cube. Then, Cu2O, a nickel source, a sulfur source and a surfactant are solvent-thermally synthesized into a Cu2S@NiS2 bimetallic sulfide. In the solvent-thermal process, an organic solvent ethylene glycol can be used as a reaction solvent, which provides a good homogeneous reaction environment for the reactants, so that the reactant molecules can fully contact each other. At the same time, in the crystallization process, a surfactant polyvinylpyrrolidone (PVP) can be adsorbed on the surface of the crystal nucleus, and ethylene glycol will also be adsorbed on the crystal nucleus to a certain extent. The combined action of the two will change the growth rate and growth direction of the crystal nucleus. PVP affects crystallization through a steric hindrance effect, and ethylene glycol uses its interaction with Cu2O and a nickel source (such as hydrogen bonds) to adjust, and finally forms a two-dimensional and three-dimensional structure of a NiS2 nanosheet wrapped in a Cu2S cube. The combination of two-dimensional and three-dimensional structures can shorten the particle transmission path and achieve the effect of fast charging and discharging. At the same time, it can provide more active sites, increase the specific surface area, fully contact with the electrolyte, and improve the battery cycle stability.

[0028] The present invention provides a lithium-magnesium dual-ion battery, which uses a prepared cuprous sulfide @ nickel disulfide positive electrode material based on a two-dimensional nanosheet wrapped three-dimensional cube as an electrode material, and 0.4M APC-0.4M LiCl as an electrolyte to improve the current situation of poor cycle stability of lithium-magnesium dual-ion batteries. Specifically, the lithium-magnesium dual-ion battery includes a battery positive electrode, and the battery positive electrode is prepared using a cuprous sulfide @ nickel disulfide positive electrode material based on a two-dimensional nanosheet wrapped three-dimensional cube as an active material.

[0029] The lithium magnesium dual ion battery also includes an electrolyte, which is an APC-LiCl electrolyte, preferably a 0.4MAPC-0.4M LiCl electrolyte.

[0030] The preparation method of the APC-LiCl electrolyte is:

[0031] S1. Dissolve anhydrous aluminum chloride in tetrahydrofuran and stir;

[0032] S2, adding phenylmagnesium chloride solution to the solution obtained in step S1, stirring, and then obtaining (all-phenyl complex) APC electrolyte;

[0033] S3. Add anhydrous lithium chloride to the solution obtained in step S2, and stir to obtain an electrolyte APC-LiCl.

[0034] In steps S1, S2 and S3, the stirring means that the stirring speed is 300 to 800 rpm;

[0035] In step S1, the dosage ratio of anhydrous aluminum chloride to tetrahydrofuran is 0.2667:2-4 g / mL, preferably 0.2667:3 g / mL;

[0036] In step S2, the concentration of the phenylmagnesium chloride solution is 2M, and the solvent is tetrahydrofuran;

[0037] In step S2, the volume ratio of the phenylmagnesium chloride solution to the volume ratio of the tetrahydrofuran in step S1 is 1-3:2-4; preferably 2:3;

[0038] In step S3, the concentration of anhydrous lithium chloride in the prepared electrolyte is 0.2-0.6M, preferably 0.4M.

[0039] The specific method of assembling the battery is as follows:

[0040] The cuprous sulfide @ nickel disulfide positive electrode material based on two-dimensional nanosheets wrapped in three-dimensional cubes is used as an active material and mixed with conductive carbon black and PVDF in a ratio of 8:1:1 or 7:2:1. It is evenly dispersed in PVDF by magnetic stirring for 6 to 8 hours. The prepared slurry is applied on copper foil using a coater, placed in a vacuum drying oven at 60 to 80°C, and pressed using a tablet press after drying for 12 to 24 hours. It is then cut into a small circular electrode sheet using a sheet cutter. The prepared electrode sheets are assembled into button batteries in a glove box filled with high-purity argon and with a water and oxygen value of ≤0.01ppm. The purity of the magnesium foil is Mg≥99.99%, the thickness is 70μm, and it is cut into the size of a gasket. The purity of the copper foil is Cu≥99.99%, the thickness is 0.5nm, and it is cut into the size of an electrode sheet. The specific method of assembling the battery is: drop a drop of electrolyte on the motor housing and place the electrode sheet, then drop two drops of electrolyte and place the glass fiber, drop three drops of electrolyte on the glass fiber and place a magnesium sheet as the counter electrode, then put in a gasket and a spring, use a MSK-110 small manual button battery sealing machine to press and seal the battery, and leave it for 6 to 10 hours.

[0041] In the preparation method of the Cu2S@NiS2 material based on two-dimensional nanosheets wrapped in three-dimensional cubes provided by the present invention, copper salt and sodium hydroxide are used as raw materials to synthesize new copper hydroxide, which is used to oxidize glucose to synthesize Cu2O; then Cu2O is mixed with a nickel source, TAA and PVP in ethylene glycol, and Cu2S@NiS2 bimetallic sulfide is obtained by one-step solvothermal treatment. As a non-toxic and low-cost material, Cu2S not only has better thermal stability than many Cu-S compounds (CuS, Cu9S5, Cu7S4, etc.), but is also a highly conductive material (~104S cm -1 ). However, the cycle performance of Cu2S is unstable. On this basis, the present invention grows NiS2 nanosheets on its surface. The synergistic effect of two different metals can improve the electronic transport performance of the material, effectively shorten the ion and electron transport paths, and greatly alleviate the volume changes caused by the battery during the charging and discharging process, thereby increasing the battery capacity and making the battery have better stability. At the same time, the interaction between different metal elements in bimetallic sulfides and the unique structure will form rich redox reaction active sites. These active sites can enhance the interaction between the electrode material and the electrolyte, promote charge transfer and ion diffusion, and improve the electrochemical performance of the battery. In addition, the 0.4MAPC-0.4M LiCl electrolyte has good stability, low overpotential, and achieves reversible magnesium deposition and stripping. The appropriate concentration of LiCl contained in the electrolyte will react with the positive electrode material Cu2S@NiS2 to undergo corresponding Li +The embedding and de-embedding of Cu2S@NiS2 provide excellent capacity and show good cycle performance. In addition, the Cu2S@NiS2 material has the advantages of simple preparation method and low price.

[0042] Compared with the prior art, the Cu2S@NiS2 material prepared by the present invention has a stable structure, and the two-dimensional and three-dimensional organic combination can effectively alleviate the volume change caused by the charging and discharging process; the NiS2 nanosheets on the outside of the prepared Cu2S@NiS2 material can provide more active sites, increase the specific surface area, and improve the cycle performance; the prepared Cu2S@NiS2 material is used as a positive electrode material for a lithium-magnesium dual-ion battery, and has a high specific capacity, excellent cycle life and good rate performance; it is used in combination with 0.4M APC-0.4M LiCl electrolyte as a lithium-magnesium dual-ion battery electrolyte, and has a low overpotential and long-term cycle stability; and the raw materials of the present invention are low in price, the synthesis process is simple, and mass production can be carried out. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 This is the SEM image of Cu2O prepared in Example 1;

[0044] Figure 2 This is the SEM image of Cu2O prepared in Example 1 (enlarged view);

[0045] Figure 3 This is a low-magnification SEM image of Cu2S@NiS2 prepared in Example 1;

[0046] Figure 4 This is a high magnification SEM image of Cu2S@NiS2 prepared in Example 1;

[0047] Figure 5 TEM image of Cu2S@NiS2 prepared in Example 1;

[0048] Figure 6 TEM image of Cu2S@NiS2 prepared in Example 1 (another field of view);

[0049] Figure 7 XRD pattern of Cu2O prepared in Example 1;

[0050] Figure 8 XRD pattern of Cu2S@NiS2 prepared in Example 1;

[0051] Fig. 9 This is the SEM image of Cu2S@NiS2 prepared in Comparative Example 1;

[0052] Fig.10 This is the SEM image of Cu2S@NiS2 / Cu prepared in Comparative Example 2;

[0053] Fig.11 This is the SEM image of Cu2S@NiS2 prepared in Comparative Example 3;

[0054] Fig.12 XRD pattern of Cu2S@NiS2 / Cu prepared in Comparative Example 2;

[0055] Fig.13 This is the SEM image of Cu2S prepared in Comparative Example 4;

[0056] Fig.14 The electrolytes prepared for Examples 1, 2 and 3 were 0.4 mA cm -2 Mg||Mg symmetric battery test at current density;

[0057] Fig.15 The electrolyte prepared in Examples 1, 2 and 3 is applied to the Cu2S@NiS2 material based on two-dimensional nanosheets wrapped in three-dimensional cubes as the positive electrode material of lithium-magnesium dual-ion batteries at 0.3Ag -1 Cyclic stability test diagram under current density;

[0058] Fig.16 The electrolyte prepared in Examples 1, 2 and 3 is applied to the Cu2S@NiS2 material based on two-dimensional nanosheets wrapped in three-dimensional cubes as the positive electrode material of lithium-magnesium dual-ion batteries at 0.5Ag -1 Cyclic stability test diagram under current density (first at 0.2Ag -1 10 cycles of activation);

[0059] Fig.17 The electrolyte prepared in Examples 1, 2 and 3 is applied to the rate performance test diagram of Cu2S@NiS2 material based on two-dimensional nanosheets encapsulating three-dimensional cubes as the positive electrode material of lithium-magnesium dual-ion battery;

[0060] Fig.18 The electrolyte prepared in Example 3 is applied to cubic structure Cu2S material as the positive electrode material of lithium magnesium dual ion battery at 0.1Ag -1 Cyclic stability test diagram under current density;

[0061] Fig.19 The electrolyte prepared in Example 3 is applied to cubic structure Cu2S material as the positive electrode material of lithium magnesium dual ion battery at 0.3Ag -1 Cyclic stability test diagram under current density;

[0062] Fig. 20 The electrolyte prepared in Examples 1, 2 and 3 is applied to the Cu2S@NiS2 material based on two-dimensional nanosheets wrapped in three-dimensional cubes as the positive electrode material of lithium-magnesium dual-ion batteries at 0.2Ag -1Impedance test after 50 cycles at current density of ;

[0063] Fig.21 for Fig. 20 Enlarged view of the dashed box in the middle;

[0064] Fig. 22 N2 adsorption-desorption isotherm of Cu2S@NiS2;

[0065] Fig.23 The corresponding pore size distribution of Cu2S@NiS2. DETAILED DESCRIPTION

[0066] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0067] Unless otherwise specified, the test materials and reagents used in the following examples can be obtained from commercial sources.

[0068] If no specific techniques or conditions are specified in the examples, they can be carried out according to the techniques or conditions described in the literature in the art or according to the product instructions.

[0069] Example 1

[0070] A method for preparing a cuprous sulfide@nickel disulfide positive electrode material based on two-dimensional nanosheets encapsulating three-dimensional cubes comprises the following steps:

[0071] 1) Preparation of Cu2O: 3.992 g of Cu(CH3COO)2·H2O was weighed and dissolved in 100 mL of deionized water, then 20 mL of 6 M sodium hydroxide solution was added dropwise, and after stirring at 500 rpm for 5 minutes, 0.8 g of D(+)-glucose was added to the solution and stirred for 1 hour. The whole process was carried out in a 70°C water bath. The obtained reddish brown precipitate was washed 5 times with deionized water and ethanol, and then dried under vacuum at 60°C. The SEM image of the obtained product is shown in FIG. Figure 1 and Figure 2 As shown in Figure 2, it can be observed that Cu2O is a cubic structure with a size of about 3 to 4 μm. Figure 7 As shown, its characteristic peaks perfectly correspond to the standard card number PDF#78-2046.

[0072] 2) Preparation of Cu2S@NiS2: 0.08g Cu2O, 0.16g Ni(NO3)2·6H2O, 0.2g thioacetamide and 3g polyvinylpyrrolidone (PVP, average molecular weight 8000, K16-18) were dissolved in 40mL ethylene glycol, and then the obtained solution was placed in a 50ml Teflon-lined autoclave and kept at 200℃ for 18h. The obtained Cu2S@NiS2 sample was washed with ethanol and dried in a vacuum at 60℃. The obtained SEM was as follows Figure 3 and Figure 4 As shown in Figure 1, it can be clearly seen that the sample structure is covered with a layer of nanosheet structure, which is about 4 to 5 μm in size. Figure 5 and Figure 6 As shown in Figure 2, the outer layer of the flaky structure is also clearly shown. Figure 8 As shown, its characteristic peaks perfectly correspond to the Cu2S standard card number PDF#53-0522 and the NiS2 standard card number PDF#88-1709.

[0073] The preparation method of the 0.4M APC-0.4M LiBF4 electrolyte of Example 1 comprises the following steps:

[0074] 0.2667 g of anhydrous aluminum chloride (AlCl3, 99%, Aladdin) was dissolved in 3 mL of tetrahydrofuran (THF, Aladdin) solvent and stirred vigorously for 12 h at 800 rpm. Then, 2 mL of 2 M phenylmagnesium chloride solution (solvent: tetrahydrofuran) was dropped into the solution and then vigorously stirred with magnetic force for 12 h to obtain Mg 2+ / Li + Finally, 0.1875 g of anhydrous lithium tetrafluoroborate (LiBF4, 99.9%, Aladdin) was dissolved in the above Mg 2+ / Li + The mixed electrolyte was stirred for 12 h to obtain 0.4 M APC-0.4 MLiBF4 electrolyte.

[0075] Example 2

[0076] A method for preparing a cuprous sulfide@nickel disulfide positive electrode material based on two-dimensional nanosheets wrapping three-dimensional cubes comprises the following steps: proceed completely according to Example 1.

[0077] The preparation method of the 0.4M APC-0.4M LiTFSI electrolyte of Example 2 comprises the following steps:

[0078] 0.2667 g of anhydrous aluminum chloride (AlCl3, 99%, Aladdin) was dissolved in 3 mL of tetrahydrofuran (THF, Aladdin) solvent and stirred vigorously for 12 h at 800 rpm. Then, 2 mL of 2 M phenylmagnesium chloride solution (solvent: tetrahydrofuran) was dropped into the solution and then vigorously stirred with magnetic force for 12 h to obtain Mg 2+ / Li + Finally, 0.57417 g of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI, 99.9%, Aladdin) was dissolved in the above Mg 2+ / Li + The mixed electrolyte was stirred for 12 h to obtain 0.4MAPC-0.4MLiTFSI electrolyte.

[0079] Example 3

[0080] A method for preparing a cuprous sulfide@nickel disulfide positive electrode material based on two-dimensional nanosheets wrapping three-dimensional cubes comprises the following steps: proceed completely according to Example 1.

[0081] The preparation method of the 0.4M APC-0.4M LiCl electrolyte of Example 3 comprises the following steps:

[0082] 0.2667 g of anhydrous aluminum chloride (AlCl3, 99%, Aladdin) was dissolved in 3 mL of tetrahydrofuran (THF, Aladdin) solvent and stirred vigorously for 12 h at 800 rpm. Then, 2 mL of 2 M phenylmagnesium chloride solution (solvent: tetrahydrofuran) was dropped into the solution and then vigorously stirred with magnetic force for 12 h to obtain Mg 2+ / Li + Finally, 0.08478 g of anhydrous lithium chloride (LiCl, 99.9%, Aladdin) was dissolved in the above Mg 2+ / Li + The mixed electrolyte was stirred for 12 h to obtain 0.4 M APC-0.4 M LiCl electrolyte.

[0083] Comparative Example 1

[0084] A method for preparing a Cu2S@NiS2 positive electrode material based on nanoparticle-wrapped cubes comprises the following steps:

[0085] 1) Preparation of Cu2O: 3.992 g of Cu(CH3COO)2·H2O was weighed and dissolved in 100 mL of deionized water, and then 20 mL of 6 M sodium hydroxide solution was added. After stirring at 500 rpm for 5 minutes, 0.8 g of D(+)-glucose was added to the solution and stirred for 1 hour. The whole process was carried out in a 70°C water bath, and the obtained reddish-brown precipitate was washed several times with deionized water and ethanol, and then dried under vacuum at 60°C to obtain Cu2O cubes.

[0086] 2) Preparation of Cu2S@NiS2: 0.08g Cu2O, 0.16g Ni(NO3)2·6H2O, 0.7 g thioacetamide and 3g polyvinyl pyrrolidone (PVP) were dissolved in 40mL ethylene glycol, and then the obtained solution was placed in a 50ml Teflon-lined autoclave and kept at 200℃ for 18h. The obtained Cu2S@NiS2 sample was washed with ethanol. It was dried in a vacuum at 60℃. The SEM image of the obtained sample is shown in Fig. 9 As shown, it can be observed that due to the excessive amount of sulfur powder, the existence form of NiS2 has become granular and is disorderly arranged on the Cu2S surface.

[0087] Comparative Example 2

[0088] A preparation method based on Cu2S@NiS2 / Cu positive electrode material comprises the following steps:

[0089] 1) Preparation of Cu2O: 3.992 g of Cu(CH3COO)2·H2O was weighed and dissolved in 100 mL of deionized water, and then 20 mL of 6 M sodium hydroxide solution was added. After stirring at 500 rpm for 5 minutes, 0.8 g of D(+)-glucose was added to the solution and stirred for 1 hour. The whole process was carried out in a 70°C water bath, and the obtained reddish-brown precipitate was washed several times with deionized water and ethanol, and then dried under vacuum at 60°C to obtain Cu2O cubes.

[0090] 2) Preparation of Cu2S@NiS2 / Cu: 0.08g Cu2O, 0.16g Ni(NO3)2·6H2O, 0.1 g thioacetamide and 3g polyvinyl pyrrolidone (PVP) were dissolved in 40mL ethylene glycol, and then the obtained solution was placed in a 50ml Teflon-lined autoclave and kept at 200℃ for 18h. The obtained Cu2S@NiS2 / Cu sample was washed with ethanol. It was dried in a vacuum at 60℃. The SEM image of the obtained product is shown in Fig.10 As shown in the figure, due to the small amount of thioacetamide, the NiS2 nanosheets are not obvious, and the excess PVP reduces Cu2O to Cu. The XRD pattern is shown in Fig.12 shown.

[0091] Comparative Example 3

[0092] A method for preparing a cubic Cu2S@NiS2 positive electrode material comprises the following steps:

[0093] 1) Preparation of Cu2O: 3.992 g of Cu(CH3COO)2·H2O was weighed and dissolved in 100 mL of deionized water, then 20 mL of 6 M sodium hydroxide solution was added, and after stirring at 500 rpm for 5 minutes, 0.8 g of D(+)-glucose was added to the solution and stirred for 1 hour. The whole process was carried out in a 70°C water bath, and the obtained reddish brown precipitate was washed several times with deionized water and ethanol, and then dried under vacuum at 60°C to obtain Cu2O cubes.

[0094] 2) Preparation of Cu2S@NiS2: 0.08g Cu2O, 0.16g Ni(NO3)2·6H2O, 0.2g thioacetamide and 1g poly PVP Dissolved in 40mL ethylene glycol, the resulting solution was then placed in a 50ml Teflon-lined autoclave and kept at 200°C for 18h. The resulting Cu2S@NiS2 sample was washed with ethanol. It was dried in a vacuum at 60°C. The SEM image of the obtained product is shown in Fig.11 As shown, due to the small amount of PVP, NiS2 nanosheets cannot be composited with Cu2S.

[0095] Comparative Example 4

[0096] A method for preparing a cubic Cu2S positive electrode material comprises the following steps:

[0097] 1) Preparation of Cu2O: 3.992 g of Cu(CH3COO)2·H2O was weighed and dissolved in 100 mL of deionized water, and then 20 mL of 6 M sodium hydroxide solution was added. After stirring at 500 rpm for 5 minutes, 0.8 g of D(+)-glucose was added to the solution and stirred for 1 hour. The whole process was carried out in a 70°C water bath, and the obtained reddish-brown precipitate was washed several times with deionized water and ethanol, and then dried under vacuum at 60°C to obtain Cu2O cubes.

[0098] 2) Preparation of Cu2S: 0.08 g Cu2O, 0.3 g thioacetamide and 1 g polyvinylpyrrolidone (PVP) were dissolved in 40 mL ethylene glycol, and the resulting solution was placed in a 50 ml Teflon-lined autoclave and maintained at 200 °C for 18 h. Cu2S Sample Wash with ethanol. Dry it in vacuum at 60°C. The SEM image of the obtained product is as follows Fig.13 As shown, it still generally maintains a cubic shape, but there are certain depressions on the surface.

[0099] Example 4

[0100] The application of Cu2S@NiS2 material based on two-dimensional nanosheets wrapped in three-dimensional cubes as the positive electrode active material of lithium-magnesium dual-ion battery and 0.4M APC-0.4M LiCl as a new electrolyte for lithium-magnesium dual-ion battery, the specific process is as follows:

[0101] The product prepared in Example 3, which is based on the Cu2S@NiS2 material of three-dimensional cube wrapped by two-dimensional nanosheets, and the Cu2S positive electrode material of the cube of the product of Comparative Example 4, are respectively mixed with conductive carbon black and PVDF in a mass ratio of 8:1:1, and then magnetically stirred for 8 hours to evenly disperse them in PVDF. The prepared slurry is coated on copper foil with a coater, placed in a vacuum drying oven at 80°C, dried for 12 hours, and then pressed into sheets with a tablet press, and then cut into small circular electrode sheets with a slicer.

[0102] The prepared electrode sheets are assembled into button batteries in a glove box filled with high-purity argon and with water and oxygen values ​​≤0.01ppm. The purity of magnesium foil is Mg ≥ 99.99%, the thickness is 70μm, and it is cut into the size of gaskets. The purity of copper foil is Cu ≥ 99.99%, the thickness is 0.5nm, and it is cut into the size of electrode sheets. The specific method of assembling the battery is: place the electrode sheet after dropping a drop of electrolyte on the motor housing, then place the glass fiber after dropping two drops of electrolyte, place the magnesium sheet as the counter electrode after dropping three drops of electrolyte on the glass fiber, then put in a gasket and a shrapnel, and use the MSK-110 small manual button battery sealing machine to press and seal the battery and place it for 10 hours.

[0103] Specific test process: After assembling the magnesium-lithium dual-ion half-battery, set the working steps on the Xinwei tester, first discharge at a constant current to 0.01V, then charge at a constant current to 2V, and repeat this cycle for a certain number of times.

[0104] During battery assembly, the electrolytes used were those prepared in Examples 1 to 3, respectively.

[0105] The test results and data are as follows:

[0106] Fig.14 Symmetrical Mg||Mg cell tests of 0.4M APC-0.4M LiCl, 0.4M APC-0.4M LiBF4 and 0.4M APC-0.4MLiTFSI electrolytes demonstrated that 0.4M APC-0.4M LiCl, as a lithium-magnesium dual-ion battery electrolyte, has a low overpotential and long-term cycling stability, indicating that the uniform deposition and extraction of magnesium has a minimal nucleation barrier.

[0107] Fig.15The electrolytes of 0.4M APC-0.4M LiBF4, 0.4M APC-0.4M LiTFSI and 0.4M APC-0.4M LiCl were applied to the Cu2S@NiS2 material with three-dimensional cubes wrapped by two-dimensional nanosheets prepared in Example 1 as the positive electrode material of lithium-magnesium dual-ion batteries at 0.3Ag -1 Cyclic stability test chart under current density. After 100 cycles, the battery capacity of 0.4M APC-0.4MLiCl as the electrolyte remains at 317mAhg -1 , while the battery specific capacities of 0.4M APC-0.4M LiBF4 and 0.4M APC-0.4MLiTFSI as electrolytes remained at 181 and 252 mAh g, respectively. -1 .

[0108] Fig.16 The electrolytes of 0.4M APC-0.4M LiBF4, 0.4M APC-0.4M LiTFSI and 0.4M APC-0.4M LiCl were applied to the Cu2S@NiS2 material with three-dimensional cubes wrapped by two-dimensional nanosheets prepared in Example 1 as the positive electrode material of lithium-magnesium dual-ion batteries at 0.5Ag -1 Cyclic stability test diagram under current density (first at 0.2Ag -1 After 200 cycles, the battery capacity of 0.4M APC-0.4M LiCl as the electrolyte remained at 260mAhg -1 , while the battery specific capacities of 0.4MAPC-0.4M LiBF4 and 0.4MAPC-0.4M LiTFSI as electrolytes remained at 142 and 227 mAh g, respectively. -1 .

[0109] Fig.17 The electrolytes of 0.4M APC-0.4M LiBF4, 0.4M APC-0.4M LiTFSI and 0.4M APC-0.4M LiCl were applied to the Cu2S@NiS2 material with three-dimensional cubes wrapped by two-dimensional nanosheets prepared in Example 1 as the positive electrode material of lithium-magnesium dual-ion battery. -1 The activation was carried out for 10 cycles at a current density of 0.5, 0.8, 1.0, and 1.5 Ag. -1 Rate performance test diagram under current density. Under the second rate gradient, the specific capacity of 0.4M APC-0.4M LiCl electrolyte is 343mAhg -1 (0.5Ag -1 ), 311mAh g -1 (0.8Ag -1 )、301mAhg-1 (1.0Ag -1 )、249mAhg -1 (1.5Ag -1 ). Both are higher than the specific capacity of 0.4M APC-0.4M LiBF4 and 0.4M APC-0.4M LiTFSI.

[0110] Fig.18 The electrolyte of 0.4M APC-0.4M LiCl is applied to the cubic structure Cu2S material as the positive electrode material of lithium magnesium dual ion battery in 0.1Ag -1 Cyclic stability test diagram under current density. After 50 cycles at this current density, the specific capacity remains at 166 mAh g -1 .

[0111] Fig.19 The electrolyte of 0.4M APC-0.4M LiCl is applied to the cubic structure Cu2S material as the positive electrode material of lithium magnesium dual ion battery in 0.3Ag -1 Cyclic stability test diagram under current density. After 200 cycles at this current density, the specific capacity remains at 28 mAh g -1 .

[0112] Fig. 20 The APC electrolyte and the electrolytes prepared in Examples 1, 2 and 3 are applied to the Cu2S@NiS2 material based on two-dimensional nanosheets wrapped in three-dimensional cubes prepared in Example 1 as the positive electrode material for lithium-magnesium dual-ion batteries at 0.2Ag -1 The impedance test after 50 cycles at the current density of Fig.21 yes Fig. 20 The enlarged image of the dotted box in the middle. After 50 cycles, the impedance of the battery with APC-LiCl as the electrolyte is the smallest at 91.3Ω, while the impedance of the battery with APC-LiBF4 as the electrolyte is 169.4Ω. The impedances of the other two electrolytes are greater than 10 4 Ω. The preparation method of the APC electrolyte is as follows: 0.2667g of anhydrous aluminum chloride (AlCl3, 99%, Aladdin) is dissolved in 3mL of tetrahydrofuran (THF, Aladdin) solvent, and vigorously stirred for 12h at 800rpm. Then, 2mL of 2M phenylmagnesium chloride solution (solvent is tetrahydrofuran) is dripped into the solution, and then vigorously magnetically stirred for 12h to obtain an electrolyte, which is the APC electrolyte.

[0113] Fig. 22 N2 adsorption-desorption isotherm of Cu2S@NiS2 prepared in Example 1, Fig.23 is the corresponding pore size distribution. The specific surface area of ​​Cu2S@NiS2 is 9.4m2 g -1 , and the average pore size is 8.56 nm, indicating that the large surface area and rich porosity of the sample provide more active sites, which is beneficial to electron / ion transfer.

[0114] The underlined data above do not meet the requirements of the present invention.

[0115] The material structure prepared by the present invention realizes the combination of two-dimensional nanosheets and three-dimensional cubes, has a large specific surface area and average pores, provides more active sites, and is fully in contact with the electrolyte, thereby significantly improving the performance of the battery. At the same time, the 0.4mol / L APC-0.4mol / L LiCl electrolyte has a low overpotential and stable cycle performance. The material is applied to the positive electrode material of lithium-magnesium dual-ion batteries combined with 0.4mol / L APC-0.4mol / L LiCl as the electrolyte, and has the advantages of good cycle performance and high energy density.

[0116] The underlined ones do not meet the requirements of the present invention.

[0117] The description of the above embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the protection scope of the present invention.

Claims

1. A method for preparing a cuprous sulfide@nickel disulfide positive electrode material based on two-dimensional nanosheets encapsulating three-dimensional cubes, comprising the following steps: 1) Preparation of Cu2O cubes; 2) Cu2O cubes, nickel source, sulfur source and surfactant are mixed in an organic solvent and subjected to solvothermal treatment to obtain Cu2S@NiS2.

2. The preparation method according to claim 1, characterized in that: In step 1), the method for preparing Cu2O cubes is: disperse the copper source in water, add alkaline solution dropwise thereto, stir, add reducing agent, and heat to react to obtain the result.

3. The preparation method according to claim 1, in step 2), the mass ratio of the Cu2O cubes to the nickel source is in the range of 2:1 to 1:

2.

4. The preparation method according to claim 1 or 3, in step 2), the mass ratio of the nickel source, the sulfur source and the surfactant is 4:3-5:60-80.

5. The preparation method according to claim 1 or 4, wherein in step 2), the sulfur source is thioacetamide and the surfactant is polyvinyl pyrrolidone.

6. The preparation method according to claim 1, in step 2), the organic solvent is ethylene glycol.

7. The preparation method according to claim 1, in step 2), the solvent thermal reaction conditions are 160-200°C for 18-24h.

8. A cuprous sulfide@nickel disulfide cathode material based on two-dimensional nanosheets encapsulating three-dimensional cubes prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The cuprous sulfide@nickel disulfide positive electrode material based on two-dimensional nanosheets wrapping three-dimensional cubes has a size of 4 to 6 μm, wherein Cu2S is the core and NiS2 is the shell; the outer NiS2 nanosheets have a thickness of 70±5 nm for each layer of the nanosheets.

9. A lithium-magnesium dual-ion battery, characterized in that: The cuprous sulfide@nickel disulfide positive electrode material based on two-dimensional nanosheets wrapping three-dimensional cubes as described in claim 8 is used as an electrode material.

10. The lithium-magnesium dual-ion battery according to claim 9, characterized in that: The lithium magnesium dual ion battery uses 0.4MAPC-0.4M LiCl as the electrolyte.

Citation Information

Patent Citations

  • Cuprous oxide / cuprous sulfide / nickel sulfide three-layer photoelectrode and preparation and application thereof

    CN111286753A

  • Preparation method of lithium battery negative electrode material nano cuprous sulfide

    CN117105259A

  • Nano coralline CuS-NiS compound negative electrode material and preparation method and application thereof

    CN117373845A

  • Nanostructured materials for electrochemical conversion reactions

    US20140170493A1